Optimization of Technological Process Management in Plant Growing - A. Yu. Izmailov; Ya. P. Lobachevsky; V. K. Khoroshenkov; I. G. Smirnov; N. T. Goncharov; Ye. S. Luzhnova (Сельскохозяйственные машины и технологии, 2018)
At the current development stage of agricultural production, agricultural enterprises are faced with precedent pressure from the market. (Research of purpose) Optimize the control parameters of agricultural production by introducing the latest technologies, reducing costs and ensuring more efficient production management. (Materials and methods) The elaboration of a centralized unified automated information management system for mobile units and stationary processes incorporates the following components: Automation of the technological process with the possibility of locating every mobile machine, tractor, combiner harvester, any other vehicle, or fixed object in the field; Transferring integrated process parameters to the dispatch center server, transforming these parameters into a convenient form for technologists, agronomists, and managerial staff; Transferring control commands to adjust the process by its performers (operators). (Results and discussion) The authors have developed agricultural production systems of a new generation to ensure the productivity level of agrocenoses with high efficiency of invested funds and the use of landscape capacity. The basic prerequisite here is that the productivity of plants depends, first of all, on the soil content of mineral nutrients with their optimum ratio in each elementary field section, as well as a set of crop protection measures. (Conclusions) Increased production and cost reduction cannot be achieved without the introduction of the latest informationbased automated control systems for production processes based on network technologies for gathering, collecting, analyzing relevant data and developing optimal management decisions. Especially important in agricultural production is the intensity rate of machinery utilization, as well as the line balance and consistency of manufacturing processes.